The Long-run Impact of Orphanhood - Beegle, Kathleen; De Weerdt, Joachim; Dercon, Stefan (World Bank, Washington, DC, 2012)
This paper presents unique evidence that orphanhood matters in the long run for health and education outcomes, in a region of Northwestern Tanzania. The paper studies a sample of 718 non-orphaned children surveyed in 1991-94, who were traced and re-interviewed as adults in 2004. A large proportion, 19 percent, lost one or more parents before the age of 15 in this period, allowing the authors to assess the permanent health and education impacts of orphanhood. The analysis controls for a wide range of child and adult characteristics before orphanhood, as well as community fixed effects. The findings show that maternal orphanhood has a permanent adverse impact of 2 cm of final height attainment and one year of educational attainment. Expressing welfare in terms of consumption expenditure, the result is a gap of 8.5 percent compared with similar children whose mother survived till at least their 15th birthday.